RESTSERV: restaurant service quality model for Malaysia / Ishmael Kelvin Jensen, Sharina Osman and Che Rosmawati Che Mat - Jensen, Ishmael Kelvin; Osman, Sharina; Che Mat, Che Rosmawati (UiTM Press, 2024)
This paper aimed to assess the culture, cultural value, and service quality perceptions of Malaysians in the restaurant industry. The literature review revealed culture and value are separate factors, but they are related to service quality. A 32-item Likert scale questionnaire was developed and distributed to Malaysian restaurants in the peninsular and East Malaysia. A total of 396 participants responded to the questionnaires. After thorough examinations of the research instrument through SmarthPLS, findings revealed six items were dropped, and all variables met the accepted criteria. Thus, this paper has developed RESTSERV, as a tool to measure service quality in the Malaysian restaurant industry.